CT-determined tricuspid annular dilatation is associated with persistence of tricuspid regurgitation after transcatheter aortic valve replacement. (3rd October 2022) - Loew, K; Steffen, J; Theiss, H; Orban, M; Rizas, K; Hagl, C; Massberg, S; Hausleiter, J; Braun, D; Deseive, S
Abstract: Introduction: Moderate or severe tricuspid regurgitation (TR) can be observed in 11% to 27% of patients with severe aortic stenosis (AS) undergoing transcatheter aortic valve replacement (TAVR). Even though in most patients an improvement of TR can be achieved after TAVR, the persistence of severe or massive TR after the procedure is associated with increased all-cause mortality. Purpose: The aim of this study was to investigate if tricuspid annular dilatation (TAD) measured in pre-procedural CT among TAVR patients who had at least moderate TR at baseline could serve as a predictor for the persistence of TR. Moreover, the predictive value of TR persistence on the composite of 2-year mortality or tricuspid valve intervention was analysed. Methods: We examined 151 patients with severe AS and at least moderate concomitant TR at baseline, who were treated with TAVR from April 2013 to December 2019. TR persistence was defined as the same or a higher grade of TR in the follow-up echocardiography at least 30 days after the procedure compared to preprocedural TR grade. To identify patients with TAD, the maximum septolateral diameter of the tricuspid annulus was measured in pre-procedural cardiac computed tomography images and normalized to the body surface area. Results: The median value of 25.5 mm/m 2 was determined as cut-off value for TAD. Out of 151 patients with moderate or more TR before TAVR, 75 patients (49.7%) were above the threshold of 25.5 mm/m 2 . Improvement of TR after TAVR of at least one grade was significantly more frequent in patients without TAD than with TAD (59% vs. 32%, corresponding odds ratio for persistence of TR: 3.06, 95% confidence interval: 1.50–6.35, p=0.001) (Figure 1A). Multivariable logistic regression analysis with adjustment for baseline TR severity confirmed that the predictive value of TAD for TR persistence after TAVR was irrespective of baseline TR (adjusted odds ratio: 2.79, 95% confidence interval: 1.42–5.59, p=0.003). Tricuspid valve intervention was conducted in 11 patients with TAD after TAVR (14.6%) and in no patients without TAD. Accordingly, at 2-years, tricuspid valve intervention-free survival was lowest among patients with TAD and persistent TR (Figure 1B). Conclusion: Our analysis demonstrates for the first time that in patients undergoing TAVR for severe AS and at least moderate concomitant TR, CT-derived TAD is associated with persistence of TR after the procedure. Furthermore, TR persistence is associated with an adverse outcome. Funding Acknowledgement: Type of funding sources: None.